Sistem Pendukung Keputusan Untuk Penentuan Jumlah Produksi Nanas Menggunakan Metode Fuzzy Tsukamoto - Agus Prayogi; Edy Santoso; Sutrisno Sutrisno (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Great Giant Pineapple is one of the agro industry companies. This company performs activities ranging from pineapple cultivation to canning process. The problem faced by PT.Great Giant Pineapple is if there is excessive production then the pineapple will be placed in the storage warehouse as the supply and the pineapple has a consumption period that does not last long and can not be consumed because the pineapple has expired due to pineapple production in the storage warehouse too long. If there is a shortage of pineapple production then customers will be disappointed because the pineapple you want to buy is up. So, with it the company will lose customers and lose. Tsukamoto's method is an extension of monotonous reasoning. In the Tsukamoto method, every consequence of the IF-THEN rules must be represented by a fuzzy set with membership function. As a result, the inference output of each rule is given explicitly (crisp) based on the Î±-predicate (fire strength). The raw material inventory and the number of requests are used as variables that will be represented by the fuzzy membership function. Furthermore, fuzzy Tsukamoto method to determine the amount of production applied in Decision Support System (SPK), then SPK will process the data with Tsukamoto method and will display the output (output) in the amount of goods to be produced. Based on the results of accuracy testing obtained error value of small forecasting results that is 0,0607%. The results given by the Fuzzy Tsukamoto method are in conformity with the results of the data of PT. GGC with error value 0,0607%..